2009
DOI: 10.1007/s00425-009-1042-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species-generating enzymes and hydrogen peroxide during cadmium, mercury and osmotic stresses in barley root tip

Abstract: The effect of cadmium (Cd) on the expression and activity of NADPH oxidase, peroxidase and oxalate oxidase as well as on the expression of aquaporins and dehydrins was studied in barley root tip. The root tip represented intact apical part of the barley root containing the root cap, meristems and elongation zone. Except stress induced by Cd, barley root tips were analysed after their exposure to phytotoxic concentration of mercury (Hg)-, hydrogen peroxide (H2O2)- or polyethylene glycol (PEG)-induced water stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 62 publications
1
37
0
2
Order By: Relevance
“…Our results showed that in addition to the activation of IAA-POD activity by exogenously added IAA also H 2 O 2 is involved in the activation of IAA-POD. The generation of ROS by several enzymes is a general syndrome of plants under Cd stress (Garnier et al 2006;Ortega-Villasante et al 2007;Tamás et al 2010). In barley, we have previously reported that both superoxide and hydrogen peroxide production was markedly induced at the presence of Cd (Tamás et al 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results showed that in addition to the activation of IAA-POD activity by exogenously added IAA also H 2 O 2 is involved in the activation of IAA-POD. The generation of ROS by several enzymes is a general syndrome of plants under Cd stress (Garnier et al 2006;Ortega-Villasante et al 2007;Tamás et al 2010). In barley, we have previously reported that both superoxide and hydrogen peroxide production was markedly induced at the presence of Cd (Tamás et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In spite of that Cd is a non-redox-active metal, it has been suggested that one of the key factors responsible for these changes is the alteration in ROS production. Apart from the Cd-induced inhibition of antioxidant systems, the enhanced production of ROS has been reported through the activation of ROS-generating enzymes including NADPH oxidase, oxalate oxidase and extracellular PODs (Garnier et al 2006;OrtegaVillasante et al 2007;Tamás et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In different studies, a correlation between growth reduction and increased lignin content in roots has been considered as a typical event in defense against metal stress in different plant species [7985]. Lignification can limit the cell expansion, the capacity for nutrient uptake and thus the ability to sustain plant growth [47].…”
Section: Interference Of Metals With Physiological Functions Of Asamentioning
confidence: 99%
“…Moreover, the lignin biosynthesis related enzymes, peroxidases and laccases were enhanced during Cd treatment [82]. Tamás et al [85] showed in barley seeds ( Hordeum vulgare ) exposed to 1 mM CdCl 2 that stress activated several H 2 O 2 generating enzymes, e.g., NADPH-oxidase, which probably contributes to general stress induced morphological changes of barley root tips, such as root thickening, cell wall modifications and lignification. These responses were accompanied by root growth inhibition due to the enhanced rigidification of cell wall and accelerated differentiation of root cells [85].…”
Section: Interference Of Metals With Physiological Functions Of Asamentioning
confidence: 99%
“…At high concentrations in soil, Hg can poison plant cells and cause physiological disorders [8], producing detrimental effects on plant growth and metabolism [9], [10]. Hg accumulation in roots prevents the uptake and transport of other mineral nutrients [11], and excess Hg in solution culture can inhibit biomass production [5].…”
Section: Introductionmentioning
confidence: 99%